Development of academics and higher education futures. - Ling, Peter (Swinburne University of Technology, 2009)
This report results from an examination of current arrangements for the development of academics as teachers in Australian higher education, and a re-evaluation of how we organise for and approach academic development more generally. The report documents current approaches to development of academics and related activities in Australian universities, including organisational arrangements and development strategies; identifies emerging issues and challenges that are likely to influence the development of academics in Australian higher education; provides recommendations to begin to address the emerging issues and challenges.